SPECIAL DEVICE FOR CONTINUOUS DECELERATION OF FREIGHT CABLEWAY TRUCKS - Martin MANTIČ; Jozef KUĽKA; Melichar KOPAS; Eva FALTINOVÁ; Ján PETRÓCI (Scientific Journal of Silesian University of Technology. Series Transport)
This paper is focused on the design of an auxiliary braking device for freight cableway trucks. The device provides continuous deceleration for the trucks before they arrive at the unloading station. It presents an alternative to manual deceleration, which poses safety hazards and is therefore a less suitable option. The design distinctly accommodates the spatial disposition at the unloading station and involves minimal interventions to the existing steel structure. Above all, it aims to increase safety by eliminating the need for human input in the process of decelerating the trucks before they are emptied. The proposed design solution was successfully applied in a real operation.